2021
DOI: 10.3389/fpls.2021.663180
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Proteomic Analysis of Smoke-Drying and Shade-Drying Processes of Postharvest Rhubarb: A Comparative Study

Abstract: Postharvest processing plays a very important role in improving the quality of traditional Chinese medicine. According to previous studies, smoke-drying could significantly promote the accumulation of the bioactive components and pharmacological activities of rhubarb, but so far, the molecular mechanism has not been studied yet. In this research, to study the molecular mechanisms of postharvest processing for rhubarb during shade-drying and smoke-drying, label-free proteomic analyses were conducted. In total, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…), flavonoids and phenolic acids are important antioxidant secondary metabolites under the action of adversity stress, is an important material basis for the plant's adversity (insect pests, water, temperature or heavy metals, and other environmental stress due to) to enhance the ability of its resistance to external stress, and the drying for the role of the harvested fresh roots and stems of plants in the process of the process of the substance that is under the environment of loss of water on the plants to produce a stressful effect ( Abascal, Ganora, & Yarnell, 2005 ; Song et al, 2016 ). Drying can timely remove the free water within the A. mongolicum Regel to avoid mould, insects and the decomposition and destruction of the active ingredients, which is conducive to storage and transport, and extend the shelf life, while many studies have confirmed that the drying process of the plant body is subjected to water loss of the adversity of the stress, which will cause intracellular changes in metabolites such as proteins, amino acids, sugars, and so on, and the plant body to cope with the adversity of water loss of the stress of the response mechanism involves a variety of metabolites and metabolic pathways ( Liang et al, 2021 ). A broadly targeted metabolomics study to reveal the transformation mechanism of active compounds in Cistanche during the drying process revealed that the biosynthesis of key metabolites, such as phenylalanine and flavonoids, was significantly enhanced during the drying process, and the production of amino acids and unsaturated fatty acids increased in Cistanche, suggesting that there is a reciprocal transformation relationship between the primary and secondary metabolites of Cistanche ( Ai, Zhang, Li, Sun, & Liu, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), flavonoids and phenolic acids are important antioxidant secondary metabolites under the action of adversity stress, is an important material basis for the plant's adversity (insect pests, water, temperature or heavy metals, and other environmental stress due to) to enhance the ability of its resistance to external stress, and the drying for the role of the harvested fresh roots and stems of plants in the process of the process of the substance that is under the environment of loss of water on the plants to produce a stressful effect ( Abascal, Ganora, & Yarnell, 2005 ; Song et al, 2016 ). Drying can timely remove the free water within the A. mongolicum Regel to avoid mould, insects and the decomposition and destruction of the active ingredients, which is conducive to storage and transport, and extend the shelf life, while many studies have confirmed that the drying process of the plant body is subjected to water loss of the adversity of the stress, which will cause intracellular changes in metabolites such as proteins, amino acids, sugars, and so on, and the plant body to cope with the adversity of water loss of the stress of the response mechanism involves a variety of metabolites and metabolic pathways ( Liang et al, 2021 ). A broadly targeted metabolomics study to reveal the transformation mechanism of active compounds in Cistanche during the drying process revealed that the biosynthesis of key metabolites, such as phenylalanine and flavonoids, was significantly enhanced during the drying process, and the production of amino acids and unsaturated fatty acids increased in Cistanche, suggesting that there is a reciprocal transformation relationship between the primary and secondary metabolites of Cistanche ( Ai, Zhang, Li, Sun, & Liu, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plants preferentially accumulate dihydroxy B-ring substituted flavonoids, which are effective scavengers of reactive oxygen species, under severe stress conditions ( Agati et al, 2011 ). It was found that the drying process caused a strong stressful effect on rhubarb, thereby promoting the synthesis and accumulation of phenolic acids and anthraquinone in rhubarb ( Liang et al, 2021 ). Respiration plays a very important role in the carbon cycle and energy metabolism of plants, which can provide sufficient energy for plant life activities and substrates for the synthesis of secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers highlight the greater volatility of ATQ and anthracene with respect to the rest of PAHs that make them more sensitive to variations in the temperature and ventilation used in smoking. Liang et al (2021) investigated the molecular mechanisms involved in the accumulation of medically active ingredients, such as anthraquinones, during post-harvest processing of rhubarb. Anthraquinone levels in rhubarb are related to the response to stress episodes in the plant, and they evidenced that a similar physiological process that occurred during drying that would explain the higher levels of anthraquinone in smoked rhubarb versus shade drying.…”
Section: Exposure and Risk Assessmentmentioning
confidence: 99%